만성 폐쇄성 폐질환 환자에서 기관지확장제의 사용에 따른 단독 폐용적 반응 (isolated volume response)과 GOLD 분류와의 관계 - 허규영; Gyu Young Hur; 이승현; Seung Hyeun Lee; 정진용; Jin Yong Jung; 김세중; Se Joong Kim; 이경주; Kyoung Ju Lee; 이은주; Eun Joo Lee; et al. (Tuberculosis and respiratory diseases, 2005)
Background : Chronic obstructive lung disease is characterized by smoke-related, gradually progressive, fixed airflow obstructions. However, some studies suggested that a reversible bronchial obstruction is common in chronic obstructive lung disease. Such reversibility persists despite the continued treatment with aerosolized bronchodilators and it appears to be related to the diminution in symptoms. The isolated volume response to a bronchodilator is defined as a remarkable increase in the FVC in response to the administration of a bronchodilator whereas the $FEV_1$ remains unchanged. This has been suggested in patients with severe emphysema. Therefore, the aim of this study was to determine the relationship between the response to a bronchodilator and the severity of an airflow obstruction in COPD patients using the GOLD classification. Methods : This study examined 124 patients with an airway obstruction. The patients underwent spirometry, and the severity of the airflow obstruction was classified by GOLD. The response groups were categorized by an improvement in the FVC or $FEV_1$ > 12%, and each group was analyzed. Results : Most subjects were men with a mean age of $65.9{±}8.5$ years. The mean smoking history was $41.26{±}20.1$ pack years. The isolated volume response group had relatively low $FEV_1$ and FVC values compared with the other groups. (p<0.001) Conclusion : In this study, an isolated volume response to a bronchodilator is a characteristic of a severe airway obstruction, which is observed in patient with a relatively poorer baseline lung function. 배 경 : 만성 폐쇄성 폐질환은 기관지 천식과 달리, 흡연과 연관이 있으며, 서서히 진행하는 고정된 기류제한을 특징으로 한다. 그러나 여러 연구에서 기류폐쇄의 가역성은 만성 폐쇄성 폐질환 환자에서도 흔히 관찰되며, 지속적으로 흡입성 기관지확장제로 치료하였을 때에도 이러한 가역성이 보여, 증상의 경감과도 관련이 있는 것으로 생각된다. 지금까지 기관지 확장제의 반응정도와 질환의 중증도를 확인하는 연구는 없었으며, 이번 연구는 만성 폐쇄성 폐질환 환자에서 기류폐쇄의 정도와 기관지 확장제의 반응정도의 상관성을 GOLD 분류법을 통해 분석하였다. 방 법 : 만성 폐쇄성 폐질환 환자들로 1초간 노력성 호기량의 노력성 폐활량에 대한 비($FEV_1/FVC$)가 0.7 이하인 경우를 대상으로 하여 GOLD 분류법과 기관지확장제 반응 여부에 따라 분류하였다. 기관지확장제 사용후 1초간 노력성 호기량, 노력성 폐활량의 변화정도에 따라 단독 용적 반응군, 단독 기류 반응군, 기류-용적반응군, 비반응군으로 나누어 분석하였다. 결 과 : 대상환자는모두124명으로, 평균연령은 $65.89{±}8.43$세 였다. 기관지확장제에 반응을 보였던 반응군이 기관지확장제에 반응을 보이지 않았던 비반응군에 비해 폐기능 검사 수치들이 통계적으로 유의한 수준으로 낮았으며, 반응군이 비반응군에 비해 GOLD 단계의 중증도가 더 높은 소견을 보였다.